Allocative efficiency measurement revisited: do we really need input prices? - Oleg Badunenko; Michael Fritsch; Andreas Stephan (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2006)
The traditional approach to measuring allocative efficiency is based on input prices, which are rarely known at the firm level. This paper proposes a new approach to measure allocative efficiency which is based on the output-oriented distance to the frontier in a profit - technical efficiency space - and which does not require information on input prices. To validate the new approach, we perform a Monte-Carlo experiment which provides evidence that the estimates of the new and the traditional approach are highly correlated. Finally, as an illustration, we apply the new approach to a sample of about 900 enterprises from the chemical industry in Germany.
Keywords: D61; L23; L25; L65; 330; Allocative efficiency; data envelopment analysis; frontier analysis; technical efficiency; Monte-Carlo study; chemical industry